Physiological responses of water-polo players under different tactical strategie - Botonis, P. G.; Toubekis, A. G.; Platanou, T. I. (Journal of Sports Science & Medicine, 2015)
The aim of this study was to investigate the effect of defense tactical strategy on physiological responses characterizing playing intensity in water-polo game. In the first part of the study, fourteen players were assigned to defending (n = 7) and offending (n = 7) groups and participated in nine 4-min plays applying three different defending systems: press, static-zone and zonepress, in front of the defense court of one goalpost. In the second part, 18 players participated in nine different real full court water-polo games cons sting of 3X15min of live-time playing periods. Both in defense court plays and real games, the three defense systems were played in a counterbalanced order and heart rate (HR) was continuously recorded. Additionally, in defense court plays, bloo lactate concentration (La) was measured at the end of each 4-min period. Mean HR within defense court plays was higher in press (153 +/- 10 beats.min-1) than in static-zone (140 +/- 11 beats.min-1) and zone-press (143 +/- 16 beats.min-1, p < 0.01). Furthermore, shorter amount of playing time was spent with HR .85% of HR peak in press (46.3 +/- 22.8%) than in static-zone (81.8 +/- 20.5%) and zone-press (75.7 +/- 32.0%, p < 0.01). Likewise, mean La was higher in press (6.5 +/- 2.9 mmol.l-1) than in static-zone (4.7 +/- 2.5 mmol.l-1) and zone-press (4.6 +/- 1.8 mmol.l-1, p < 0.01). In real games, however, mean HR was similar between tactical strategies (p > 0.05). Defenders and offenders showed similar HR and La responses across the tactical modes. In conclusion, defense tactical strategies affect physiological responses within a part of the game but do not affect the overall playing intensity of a real water-polo game. Tactical strategies similarly affect offenders and defenders.